The Development of 3D Survival Simulation Game for Identifying Safe Food and Water in Borneo Forest - Kurniawan, Yuda Fatah; Isnanda, Reza Giga; Asroni, Asroni (Emerging Information Science and Technology, 2020)
For adventures who like to explore the forest with diverse type of flora, such as Borneo forest, being lost and have limited supply of food and water become one of the biggest threats for survival. Therefore, it is important to know how to identify food and water that is safe for consumption. Unfortunately, the learning media for survival skills are still heavy on verbal approach, so there is a need for a more practical and visual learning media. To overcome the problem, this research was aimed to develop a survival simulation game that teach the player how to identify safe food and water in Borneo forest. The game was developed in six steps based on Luther’s steps of authoring multimedia. At the end of the development process, the feasibility of the game as learning media is tested using pre-test and post-test method. Statistical analysis using paired t-test showed that the post-test result (M=77.33, SD=5.37) was significantly higher than the pre-test result (M=56.67, SD=8.24) ); t(29)=18.49, p < 0.001. This indicates that the game is feasible in teaching the knowledge to the player. In the future, this game can be an alternative and practical solution for teaching survival skill.